Creating Of Electronic Filing System Based Microsoft Access at PT Mitra Rajawali Banjaran - Syarifatunnisa, Manda Rahima; Firmansyah, Yayan (Jurnal Computech & Bisnis (e-journal), 2023)
PT. Mitra Rajawali Banjaran (PT.MRB) is one of the subsidiaries of PT. Rajawali Nusantara Indonesia (Persero). PT.MRB is a medical equipment factory that produces various products such as condoms, syringes, gloves, and other medical devices. The company's current mail management activities still use manual methods, using handwritten agenda books as a tool for recording letters, which has some limitations in its usage. In an effort to overcome the problems that arise from manual mail management, an electronic mail management system is developed using Microsoft Access. This project aims to create an electronic archive system that can save time in recording and retrieving archives. The system development method used is the waterfall method, starting with data collection through literature study, observation, and interviews. The result of this project is a letter management application based on Microsoft Access. Based on testing and interviews with users, it was found that this system is quite effective in meeting the company's needs, including assisting in the process of archiving correspondence and searching for letters. The trial was conducted using 116 archived data for incoming and outgoing letters. 115 out of the 116 archived data were successfully found, resulting in an archival inaccuracy rate of 0.8%. This indicates that 0.8% of the evaluated archives had inaccuracies or errors in archive management. The lower the archival inaccuracy rate, the higher the accuracy and quality of archive management.